Biuret Induced Tin‐Anchoring and Crystallization‐Regulating for Efficient Lead‐Free Tin Halide Perovskite Light‐Emitting Diodes. Issue 17 (22nd March 2022) - Jia, Haoran; Shi, Hongfei; Yu, Runnan; Ma, Huanyu; Wang, Zhibin; Zou, Chao; Tan, Zhan'ao
Abstract: Lead‐free perovskite emitters, particularly 2D tin (Sn) halide perovskites, have attracted considerable academic attention in recent years. However, the problems of Sn oxidation and rapid crystallization lead to an inferior perovskite morphology with high trap states, thus limiting the luminous efficiency of Sn halide perovskite light‐emitting diodes (PeLEDs). In this study, the authors establish an approach by introducing an organic additive, 2–imidodicarbonic diamide (biuret), to address the issues of Sn oxidation and fast crystallization. The unique symmetrical carbonyl groups in the biuret robustly interact with the Sn‐I framework, providing a strong Sn‐anchoring effect. Consequently, it also suppresses the easy oxidation of Sn 2+, regulating the crystallization process simultaneously. Density functional theory (DFT) calculations also confirmed the robust interaction between the biuret and the 2D Sn halide perovskite. Furthermore, the authors demonstrate efficient PeLEDs with saturated red emission at 637 nm, a maximum luminance ( L max ) of 418 cd m −2, a maximum external quantum efficiency (EQEmax ) of 1.37%, and a half‐life ( T 50 ) of 288 s. This work provides insights on the microcosmic chemical interaction between organics and 2D Sn halide perovskites, advancing the development of efficient lead‐free PeLEDs. Abstract : 2D lead‐free tin halide perovskite light‐emitting diodes (PeLEDs) exhibit inferior device performance. Herein, the authors develop a strategy to address the problems of Sn oxidation and rapid crystallization simultaneously by incorporating an organic additive, biuret. Consequently, a high external quantum efficiency of 1.37% and high operational stability are realized in lead‐free tin halide PeLEDs.